The Incidence of Unnecessary Pancreatic Resections for Non-Cancerous Lesions: A Retrospective Study in a Thai Tertiary Hospital - Tantayanondkul, Jakarin; Luvira, Vor; Srisuk, Tharatip; Thanasukarn, Vasin; Losuwarat, Kwanchanok; Wannasri, Thitiporn; Tipwaratorn, Theerawee; Titapun, Attapol; Jarearnrat, Apiwat; Pruekprasert, Pathompong; et al. (Asian Pacific Journal of Cancer Care, 2024)
Background: Pancreatic and peri-ampullary cancers are aggressive malignancies requiring surgical intervention. However, certain non-cancerous conditions can mimic these cancers on imaging, leading to unnecessary pancreatic resections. This retrospective study investigated the incidence of non-cancerous lesions removed during pancreatic resections for suspected pancreatic or peri-ampullary cancers in a tertiary hospital in Thailand. Materials and Methods: This retrospective review was conducted on 148 patients who underwent pancreatic resection between January 2013 and December 2017 at Srinagarind Hospital, Khon Kaen University. Medical and pathological data were analyzed to determine the proportion of patients with non-cancerous lesions. Results: Nine patients (6.1%) had a postoperative diagnosis of a non-cancerous condition not requiring surgical intervention. The rate of unnecessary resections was significantly higher in patients undergoing distal pancreatectomy or enucleation (15%, 4/27) compared to those undergoing pancreaticoduodenectomy (4.1%, 5/121). While clinical features were similar between patients with cancerous and non-cancerous diagnoses for pancreaticoduodenectomy, a significant difference was observed in gender (p=0.031). No significant clinical differences were found between the two groups after distal pancreatectomy or enucleation. Conclusion: This study highlights the occurrence of unnecessary pancreatic resections for non-cancerous lesions in a Thai setting. The prevalence of these cases, particularly for distal pancreatectomy and enucleation, suggests the need for careful evaluation and diagnostic strategies to minimize unnecessary surgeries. The findings also highlight potential geographical differences in the types of non-cancerous conditions mimicking pancreatic and peri-ampullary cancers, with Eastern countries experiencing a higher prevalence of ampullary and bile duct conditions compared to Western countries. Further research is needed to develop improved diagnostic tools and refine surgical decision-making processes in this complex clinical setting.